Parametric optimization of lactic acid extraction from aqueous solution in a mixed flow reactor using emulsion liquid membrane by response surface methodology - Thakur, Avinash (Array, 2008)
A statistical programme using Box-Behnken design, which applies a response optimization algorithm, was used to calculate and optimize simultaneously the lactic acid extraction by emulsion liquid membrane (ELM) in a mixed flow reactor. A 3-level Box-Behnken design with seven variables i.e. lactic acid concentration, internal reagent concentration, Alamine 336 fraction in oleyl alcohol, stirring speed, fraction of acceptor phase containing internal reagent in emulsion, feed: emulsion ratio and residence time was used to identify a significant correlation between the effect of these variables on lactic acid extraction from aqueous phase since the conventional practice of single factor optimization by maintaining other factors at an unspecified constant level does not depict the combined effect of all the factors involved.